Molecular phylogeny of section Drosanthe (Spach) Endl. (Hypericum L.) inferred from chloroplast genome - Dogan, Gulden; Yilmaz, Asli; Bagci, Eyup; Kaya, Zeki (Pakistan Botanical Society, 2017)
The phylogenetic relationships of Drosanthe section of Hypericum genus (Hypericaceae) were analyzed by using non-coding chloroplast DNA region (trnL 3’-trnF) for 58 individuals. The section is represented by 23 taxa and nine of which are endemic to Turkey. The chloroplast phylogeny suggested that the members of this section belonged to a polyphyletic group, which imply at least two independent origins. The individuals of this section clearly formed two main clades. One clade included all members of this section except H. amblysepalum, H. spectabile, H. lysimachioides var. spathulatum and H. sorgerae. Our current phylogenetic results supported the morphological grouping in the Drosanthe section. © 2017, Pakistan Botanical Society. All Rights Reserved.
Keywords: Chloroplast DNA; Drosanthe; Hypericum; Polyphyletic; trnL 3’-trnF region